Der katholische Glaubensbegriff und Toleranz. Inspirationen von Paweł Włodkowic - Wojciech Zyzak (The Person and the Challenges. The Journal of Theology, Education, Canon Law and Social Studies Inspired by Pope John Paul II)
Paweł Włodkowic – Latin Paulus Vladimiri (1370-1435): Catholic priest, scholar, jurist, religious and political writer, rector of the Jagiellonian University, defender of Polish interests in disputes with Knights of the Teutonic Order. Paweł Włodkowic was an early teacher of the idea of tolerance, who during the Council of Constance stated that pagan nations have the right to maintain their religious beliefs. Based on the major theological authority of that time, i.e. Saint Thomas Aquinas, Włodkowic could, in the very concept of faith in the Catholic Church, see the most important elements requiring tolerance. The point is, above all, that faith must be an act of human freedom, that it is God’s grace and that it is closely related to reason. These elements have been commented on by authorities such as Edith Stein and Joseph Ratzinger.